MENGELOLA BISNIS USAHA KECIL MENENGAH DI MASA PANDEMI - Heru Cahyo; Siti Muntahanah (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of Community Service activities is to increase knowledge and improve skills in marketing products and managing finances for Small and Medium Enterprises to survive the pandemic in Srikandi Village, Purworejo Klampok District, Banjarnegara Regency. The method used in this service is counseling and question and answer for the community, especially Small and Medium Enterprises. The results of this community service activity, the community, especially Small and Medium Enterprises, can increase their knowledge and understanding of product marketing strategies and strategies for managing business finances. With this activity, the community is able to market products effectively and the community is able to manage finances in a disciplined manner so that the business performance can be monitored and developed properly. In addition, the need for assistance and motivation for Small and Medium Enterprises actors to continue to be creative in marketing products by utilizing existing technology.